E-collaboration concepts, methodologies, tools, and applications - Kock, Ned F., 1964- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2009)
"This set addresses a range of e-collaboration topics through advanced research chapters authored by an international partnership of field experts"--Provided by publisher.